The Romanian People and Cursing. Some Journalistic Opinions from the Past: Array - Teodorascu, Fanel (Acta Universitatis Danubius. Communicatio, 2021)
[The Romanian people and cursing. Some journalistic opinions from the past]. In this paper, we aim at examining precisely what some of the Romanian journalists, from the end of the 19th century and the beginning of the 20th century, were writing about cursing, as it was understood at that moment, and about those men prone to cursing. In order to conduct this research, many press articles have been read, most of them published in journals such as România liberă, Gazeta Transilvaniei, Adevărul, Țara noastră, Unirea poporului etc.